2021
DOI: 10.1186/s12992-021-00738-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of gender and women in the political economy of health in armed conflict: a narrative review

Abstract: Background The ripple effects of protracted armed conflicts include: significant gender-specific barriers to accessing essential services such as health, education, water and sanitation and broader macroeconomic challenges such as increased poverty rates, higher debt burdens, and deteriorating employment prospects. These factors influence the wider social and political determinants of health for women and a gendered analysis of the political economy of health in conflict may support strengtheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…In most settings, we found women face systematic and structural barriers to participating in and advancing leadership positions in the health system, similar to the wider literature on women's leadership in health systems [54]. Advancing women's leadership in conflict settings is exacerbated by security issues and systems wide patriarchal attitudes emboldened by the presence of conflict [47,55,56]. Lack of political will to enhance women's leadership in health, alongside the policies adopted by de facto authorities in some contexts, contributed to reversing the privileges that women have recently achieved regarding access to leadership positions.…”
Section: Women's Leadership In Health Systemssupporting
confidence: 71%
“…In most settings, we found women face systematic and structural barriers to participating in and advancing leadership positions in the health system, similar to the wider literature on women's leadership in health systems [54]. Advancing women's leadership in conflict settings is exacerbated by security issues and systems wide patriarchal attitudes emboldened by the presence of conflict [47,55,56]. Lack of political will to enhance women's leadership in health, alongside the policies adopted by de facto authorities in some contexts, contributed to reversing the privileges that women have recently achieved regarding access to leadership positions.…”
Section: Women's Leadership In Health Systemssupporting
confidence: 71%
“… 36 Our recent study shows that women’s inclusion in the political economy of health in conflict has greater dividends for sustainable peace and more equitable social economic recovery in the post-conflict period. 37 Yet, the conflict literature features very limited discussions on the important role of gender equity and equality within a broader health systems emphasis; its focus to date has been predominantly in very few post-conflict settings.…”
Section: Bridging Health and Peace Through Gender Diverse Leadership ...mentioning
confidence: 99%
“…Women Leaders in Health and Conflict Initiative research found limited evidence on the role and impact of women’s leadership at the nexus of health and conflict. 4 , 5 A move is required from often anecdotal discussion to the development of rigorous and authoritative evidence. Advocating for women’s rights can be complemented by evidencing the impact of women’s leadership on humanitarian action such as minimizing risk and better decision-making.…”
mentioning
confidence: 99%
“…7 The approach to women’s leadership must be inclusive, institutionalized and focused on intersectionality. 5 …”
mentioning
confidence: 99%